TASTE MASKING OF DIRECTLY COMPRESSED PHENYTOIN SODIUM ORALLY DISINTEGRATING TABLETS BY SOLID DISPERSION TECHNIQUE - Dangprasirt, Pienkit; Wongthongdee, Warumporn; Nimsumlee, Supatchalida; Yusop, Annus; Dangprasirt, Moleephan (Interprofessional Journal of Health Sciences, 2023)
Phenytoin sodium (PS) orally disintegrating tablets were prepared by direct compression using various contents of spray-dried lactose and microcrystalline cellulose (Avicel® PH 102) as direct compressible diluents. Crospovidone (Polyplasdone® XL), magnesium stearate and talcum were used as disintegrant, lubricant and glidant, respectively. Mannitol or sorbitol and saccharin sodium were also utilized as sweetening agents to mask the bitter taste of PS. The orally disintegrating tablet formulation that provided the fastest disintegration time and provided the satisfied drug dissolution was selected as the optimum formulation. A solid dispersion technique, coprecipitation method, was applied as an attempt to mask the bitter taste of PS from the optimum orally disintegrating tablet formulation using mannitol or sorbitol as carrier. The orally disintegrating tablets prepared by PS-sorbitol and PS-mannitol solid dispersions provided better taste than those prepared by PS-sorbitol and PS-mannitol physical mixtures. However, the dissolution of orally disintegrating tablet prepared by PS-sorbitol solid dispersion was slower than that of the orally disintegrating tablet prepared by PS-sorbitol physical mixture and did not meet the USP requirement of not less than 85% drug dissolved at the 30th minute time interval. The orally disintegrating tablets prepared by PS-mannitol solid dispersion and physical mixture exhibited comparable satisfied disintegration times of 0.13 and 0.20 minutes, respectively. Their dissolution profiles were also similar and met the USP requirement. Inclusion of menthol in the orally disintegrating tablet consisted of PS-mannitol solid dispersion improved the tablet taste due to the additional cooling sensation. The drug dissolution from this orally disintegrating tablet formulation met the USP requirement. However, the reduction in tablet dissolution rate was observed in the initial period of drug dissolution.